Influence of chemical structure on absolute odour thresholds and odour characteristics of ortho- and para-halogenated phenols and cresols - Strube, Andrea; Büttner, Andrea; Czerny, Michael (Flavour and Fragrance Journal, 2012)
Halogenated phenols and cresols belong to a group of volatiles consistently reported as off-flavour compounds. For example, 2-iodophenol and 2-iodo-4-methylphenol with their typical medicinal smell were found to negatively affect bottled mineral water. Even though these compounds are widespread in nature no comprehensive information about their chemo-analytical as well as odour properties is available. Therefore, the objective of this study were (1) to provide systematic chemo-analytical data on these substances, such as mass spectral data and retention parameters in gas chromatographic analysis, and (2) to determine, on a direct comparative basis, the sensory properties of eight mono-halogenated phenols, four di-halogenated phenols and four halogenated cresols. Evaluations focused on the determination of odour quality and odour threshold concentration in air and water. With regard to the relationship between substitution pattern and odour character, the location of an iodine atom in the ortho-position was demonstrated to obviously be an important prerequisite for medicinal, plaster-like or ink-like smell. Faecal or horse stable-like odour notes were predominantly related to compounds being substituted either by halogen moieties or by a methyl group in the para-position. The 2-halogenated 4-methylphenols were found to be the odorants with the lowest odour threshold concentrations of all the compounds investigated in this study, and that, generally, compounds with ortho-halogenation exhibited exceptionally low odour threshold concentrations. Copyright (C) 2012 John Wiley & Sons, Ltd.
Keywords: structure–odour relationship; off-flavour; medicinal; faecal; halogens